INFORMATION-ANALYTICAL COMPETENCE AS A RESPONSE TO MISINFORMATION AND DIGITAL MANIPULATION IN EDUCATION - Bakhtiyorjon Madaliyev (Bright Mind Publishing, 2026)
The rapid growth of digital platforms has intensified the circulation of misinformation and manipulative content, creating serious challenges for education systems across the world. Such exposure undermines learners’ capacity for critical thinking, decreases trust in reliable sources, and weakens democratic values. In Uzbekistan, where digitalization is expanding alongside educational reforms, the urgency of building students’ resilience against misinformation is especially clear. This article examines information analytical competence as a theoretical and pedagogical response to digital manipulation in education. Instead of presenting empirical data, the study applies a theoretical and analytical approach that synthesizes insights from international frameworks such as UNESCO’s Media and Information Literacy, the European Union’s DigComp 2.2, and the OECD’s Learning Compass, together with Uzbekistan’s educational strategies. Findings indicate that information analytical competence is not only a cognitive skillset but also a socio ethical framework enabling learners to identify, evaluate, and responsibly apply information in diverse contexts. Embedding this competence within teacher education curricula can foster sustainable pedagogical practices, promote critical thinking, and strengthen resistance to misinformation. By aligning global frameworks with national priorities, the article contributes to academic debates on digital literacy, media education, and the preparation of teachers for the challenges of the information society.
Keywords: Information-analytical competence, digital literacy, misinformation, teacher education, critical thinking, media literacy, pedagogical innovation.